Analysis of the Use of Google Classroom Applications for Simple Linear Regression Materials for Actuarial Study Program Students: Analisis Pemanfaatan Aplikasi Google Classroom untuk Materi Regresi Linier Sederhana pada Mahasiswa Prodi Aktuaria - Muchlian, Melvi; Z, Yulia Rahmawati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
This study aims to improve student learning outcomes of the actuarial study program at Tamansiswa Padang University who took regression analysis courses totaling 14 students, consisting of 2 male students and 12 female students by utilizing the Google Classroom application as a learning strategy during the Covid-19 pandemic. 19 on the material of simple linear regression. This google classroom application makes it easy for lecturers to manage learning and convey precise and accurate information to students. This type of research is classroom action research which is carried out for two cycles. Each cycle consists of stages of planning (planning), action (action), observation (observation), and reflection (reflection). Observation and testing are data collection techniques used in this study. Data reduction, data presentation, and conclusion drawing are data analysis techniques used in this study. The results of the research that has been carried out are the benefits of the google classroom application during the Covid-19 pandemic, namely the increase in student learning outcomes of the Actuarial Study Program at Tamansiswa Padang University on simple linear regression material as evidenced by the number of students who achieved a score of ≥ 65 in cycle II as many as 13 students. (92.9%) and 1 student (7.1%) got a score of ≤ 65, compared to the first cycle as many as 0 students (0%) who achieved a score of ≥ 65 and 14 students (100%) got a score of ≤ 65. Percentage of achievement the value of ≥ 65 of the students increased (cycle I was 0%, cycle II was 92.9%.